Winnipeg comedy club defends decision to book Louis C.K. despite sexual misconduct - Caruk, Holly (CBC News, 2019)
An American comedian and actor who admitted to sexual misconduct will take the stage at a Winnipeg comedy club next week but not everyone is lining up for tickets.
Keywords: Bibliographie; Nettoyer; Sophie-Anne

Double Binds and Punchlines: An Examination of Women in Stand Up Comedy and Television Writers' Rooms - Sargent, Amberia (UCLA, 2019)
In this dissertation, I examine how double binds around sexuality and gender norms shape how women navigate sexual harassment and threats to their professional identities in stand up comedy and television writers’ rooms. I explain the ways the workplace dilemmas women confront are informed by race, sexuality, physical attractiveness, tenure, and relationship status.
Keywords: Sophie-Anne

“The Destruction of a Legacy”: Agenda Setting and the Bill Cosby Sexual Assault Allegations - Terán, Larissa; Emmers-Sommer, Tara M. (Sexuality & Culture, 2018)
Utilizing agenda setting theory, this study investigates the Bill Cosby sexual assault allegation scandal and how the scandal is framed by the media. In order to examine if and how varied networks reported differently on the Cosby scandal, sixty articles from three, distinct networks (CNN, FOX News, E!) were analyzed and coded under seven different categories. Results demonstrate a significant difference among the analyzed networks and media frames most reported in the sample for this study. Although all networks address Cosby’s rise and fall of an American hero, agendas set and story frames presented varied. Specifically, CNN highlighted victims’/survivors’ powerful voice whereas E! and FOX News highlighted Cosby’s support from the black community, celebrities and co-stars. Additional results, discussion and future directions follow.
Keywords: Agenda setting theory; Bill Cosby; Mediated communication; Scandal; Sexual assault; Sophie-Anne

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec – Sommaire 2018-2: Données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Keywords: Bibliographie; Humour; Nettoyer; Sophie-Anne; Types de VACS

Not So Funny Business: Sexual Harassment in Stand-Up Comedy - Hansen, Briana (Workandmoney, 2017)
Up-and-coming Los Angeles comedian reflects on her experience of assault among some of the funniest people on the planet
Keywords: Sophie-Anne

ReadTheCode.ca - Canadian Creative Industries (2017)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

"They're Only Laughing 'Cause You're Pretty": Women's Experiences at Comedy Clubs - Lopez, Victoria Angelina (2017)
Stand-up comedy, like many forms of public entertainment or workplace organizations, is a field dominated by men. The deeply embedded perception that women are not funny, or not as funny as their counterparts, allow men’s privileged position in pursuing their career in comedy without their humor being questions based on their gender. However, the women’s’ experiences were found to be challenging with women’s humor being questioned and overshadowed by a hostile environment of sexual harassment. This disparity in the number of women represented in comedy is even more prevalent when it comes to the number of women who participate in stand-up comedy at the amateur level of open mic nights. This thesis examines gender disparity among comedians, the prejudices and discrimination women comedians face at the level of amateur comedian, and how they navigate through those barriers in comedy. Based on the findings from 14 in depth-interviews with 7 men and 7 women comedians, as well as observations of open-mic nights, this study investigates their experiences and perceptions of gender politics in comedy.
ISBN: 9780355540321
Keywords: Comedy clubs; Communication and the arts; Social sciences; Sophie-Anne

‘I Think Women are Possibly Judged More Harshly with Comedy’: Women and British Television Comedy Production - Mills, Brett; Ralph, Sarah (Critical Studies in Television, 2015)
Critics and creative workers have recently highlighted the lack of women working in British television comedy. Through thematic analysis of interviews with British television comedy professionals, this article explores how women talk about their work and their position within the industry. Outlining the specific industrial contexts within which female comedy professionals work, the article examines institutionalised gender norms and practical impediments which the interviewees' responses reveal, while also exploring the institutional and personal initiatives which they have developed to address these problems.
Publisher: SAGE Publications